2005
DOI: 10.1109/tasc.2005.849155
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between strand stability and magnet performance

Abstract: Abstract-Magnet programs at BNL, LBNL and FNAL have observed instabilities in high J c Nb 3 Sn strands and magnets made from these strands. This paper correlates the strand stability determined from a short sample-strand test to the observed magnet performance. It has been observed that strands that carry high currents at high fields (greater than 10T) cannot sustain these same currents at low fields (1-3T) when the sample current is fixed and the magnetic field is ramped. This suggests that the present genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 14 publications
3
27
0
Order By: Relevance
“…The magnetic field was swept from 0 to 16 T, and then back to 0 T again. We used fixed temperatures of 4, 4.5, 5,6,7,8,9,10,11,12,14,16,18,20,25,30,35, 40 and 76 K. Measurements at 4, 4.5, and 5 K were done in liquid helium and those at 76 K were done in liquid nitrogen. Our re-entrant Dewar can be filled with a liquid cryogen, pressurized, and heated to change the temperature of the cryogen.…”
Section: Magnetoresistance Of Resistive Thermometersmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic field was swept from 0 to 16 T, and then back to 0 T again. We used fixed temperatures of 4, 4.5, 5,6,7,8,9,10,11,12,14,16,18,20,25,30,35, 40 and 76 K. Measurements at 4, 4.5, and 5 K were done in liquid helium and those at 76 K were done in liquid nitrogen. Our re-entrant Dewar can be filled with a liquid cryogen, pressurized, and heated to change the temperature of the cryogen.…”
Section: Magnetoresistance Of Resistive Thermometersmentioning
confidence: 99%
“…In addition, some of the conductor designs and heat treatments cause the residual resistivity ratio (RRR, ratio of room temperature resistivity to the resistivity at 20 K) of the stabilizer to be less than 20. These parameters are pushing the conductors towards less intrinsic stability, into a region we call marginally stable [13][14][15][16][17]. These parameters also create a whole series of challenges for routine I c testing on short-samples, even when tested with the sample immersed in liquid helium.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetization instability has been the primary cause of the limited quench performance (40-70% of the short sample limit) at 4.4 K of some high field magnets built at FNAL [12] Manuscript and LBNL [13], [14] in the early 2000s. These magnets were characterized by a large (70-100 ), a moderately high (1700-1900 at 4.2 K and 12 T) and, a low RRR ( 10).…”
mentioning
confidence: 99%
“…These magnets were characterized by a large (70-100 ), a moderately high (1700-1900 at 4.2 K and 12 T) and, a low RRR ( 10). At present the problem of magnetization instability at 4.4 K is contained through an optimization of the heat treatments and cabling process that guarantee a high RRR ( 150).…”
mentioning
confidence: 99%
“…In the meantime, the LARP Materials Group focuses on improving magnetic stability of stateoftheart NbaSn strands. Several groups worked on this topic [5] [8], and it was experimentally shown that an effective filament diameter, d e ff, of excessive size reduces the critical current, I c , at low field to <20% of its expected value. Collaborating with strand manufacturers to reduce d e ff is therefore important.…”
Section: Introductionmentioning
confidence: 99%